BioModels Database: curation and annotation - Schubert, Michael; Ajmera, Ishan; Chelliah, Vijayalakshmi; Endler, Lukas; Rodriguez, Nicolas; Laibe, Camille; Le Novère, Nicolas (Nature precedings, 2011)
The BioModels Database is a freely accessible online resource for storing, viewing, retrieving, and analyzing published, peer-reviewed quantitative models of biological processes.In this poster we provide an overview of its capabilities, as well as the curation and annotation process with two use cases concerning blood coagulation and glucose homeostasis.